Monthly and Annual Schemes of Average, Maximum and Minimum Flows in the Itacaiúnas Hydrographic Sub-Region (SRHI) (Research, Society and Development, 2022)
Water plays a fundamental role in the structuring and development of the basin. In this sense, the present study aims to characterize the average, maximum and minimum flows in the Itacaiúnas hydrographic sub-region (SRHI). The survey of information from the fluviometric stations was carried out with the National Hydrometeorological Network of the National Water Agency - ANA, obtained from its Hidroweb portal, then the data was forwarded and processed in the Computational System for Hydrological Analysis developed by the GPRH, SisCAH 1.0. Based on the analyses, it was possible to identify that in the basin the presence of a climatic seasonality, with two well-defined characteristic periods, the rainy months corresponding from October to April when the flow values ​​tend to increase, on the other hand in the dry period that starts in May and extends until the month of September, low volumes are registered. From the studied stations, the one located in the municipality of marabá presents superior flow peaks with an annual average of 596.8 m3/s for this one installed in the Itacaiúnas basin. The lower flow values ​​were registered at the Parauapebas post, inserted in the Parauapebas river, which is a tributary of the Itacaiúnas basin and presented an annual average of 92.7 m3/s.